2023
DOI: 10.3390/pharmaceutics15061573
|View full text |Cite
|
Sign up to set email alerts
|

Development of Zeise’s Salt Derivatives Bearing Substituted Acetylsalicylic Acid Substructures as Cytotoxic COX Inhibitors

Alexander Weninger,
Jessica Sagasser,
Victoria Obermoser
et al.

Abstract: Zeise’s salt derivatives of the potassium trichlorido[η2-((prop-2-en/but-3-en)-1-yl)-2-acetoxybenzoate]platinate(II) type (ASA-Prop-PtCl3/ASA-But-PtCl3 derivatives) were synthesized and characterized regarding their structure, stability, and biological activity. It is proposed that the leads ASA-Prop-PtCl3 and ASA-But-PtCl3 interfere with the arachidonic acid cascade as part of their mode of action to reduce the growth of COX-1/2-expressing tumor cells. With the aim to increase the antiproliferative activity b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…Optimizing the interference with the COX cascade by linking Zeise’s salt to ASA was already performed. However, the resulting ASA-Alk-PtCl 3 complexes (Chart ) had only slightly higher COX-2 inhibitory activity than Zeise’s salt. , …”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Optimizing the interference with the COX cascade by linking Zeise’s salt to ASA was already performed. However, the resulting ASA-Alk-PtCl 3 complexes (Chart ) had only slightly higher COX-2 inhibitory activity than Zeise’s salt. , …”
Section: Resultsmentioning
confidence: 99%
“…However, the resulting ASA-Alk-PtCl 3 complexes (Chart 1) had only slightly higher COX-2 inhibitory activity than Zeise's salt. 33,36 It was also shown that the organometallic substructure determines the efficacy of COX inhibitors. For example, binding to a dicobalt hexacarbonyl cluster strongly enhanced the COX inhibitory effect of ASA-propargyl ligands.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 3 more Smart Citations